Interploidy hybridization barrier of endosperm as a dosage interaction - Birchler, James A. (Frontiers in Plant Science, 2014)
Crosses between plants at different ploidy levels will often result in failure of endosperm development. The basis of this phenomenon has been attributed to parental gene imprinting of genes involved with endosperm development but a review of the data from maize indicates a dosage interaction between the contributions of the female gametophyte and the primary endosperm nucleus to early endosperm development. However, it is noted that parental imprinting is a non-mutational means that can alter dosage sensitive factors and therefore can contribute to this effect. Operationally, the genes determining ploidy hybridization barrier would qualify for Dobzhansky-Muller incompatibilities that prevent gene flow between species.